Crop genome editing through tissue-culture-independent transformation methods - Sebiani-Calvo, Alejandro; Hernández-Soto, Alejandro; Hensel, Götz; Gatica-Arias, Andrés (Frontiers in Genome Editing, 2024)
Genome editing and plant transformation are crucial techniques in plant biotechnology, allowing for the precise modification of plant genomes to enhance agronomically essential traits. The advancement of CRISPR-based genome editing tools in plants is limited, among others, by developing novel in vitro tissue culture methodologies for efficient plant genetic transformation. In-planta methodologies offer a promising alternative to overcome tissue culture limitations and facilitate crops' genetic improvement. The inplanta transformation methods can be categorized under the definition of means of plant genetic transformation with no or minimal tissue culture steps meeting the conditions for minimal steps: short duration with a limited number of transfers, high technical simplicity, limited list of hormones, and that the regeneration does not undergo callus development. In this review, we analyzed over 250 articles. We identified studies that follow an in-planta transformation methodology for delivering CRISPR/Cas9 components focusing on crop plants, as model species have been previously reviewed in detail. This approach has been successfully applied for genome editing in crop plants: camelina, cotton, lemon, melon, orange, peanut, rice, soybean, and wheat. Overall, this study underscores the importance of in-planta methodologies in overcoming the limitations of tissue culture and advancing the field of plant genome editing. Keywords agriculture • CRISPR • crop improvement • in-planta transformation • genome editing 1.